Swift Cure of a Chronic Wound Infected With Multiresistant Staphylococcus aureus in an Elderly Patient With Stage 5 Renal Disease. (June 2019) - Kyriakopoulos, Anthony M.; Grapsa, Eirini; Marcinkiewicz, Janusz; Nagl, Markus
We present a case of a 91-year-old female with stage 5 renal disease, diabetes type 2, and considerable weakness, suffering from a 2-month-old wound infected by a multiresistant Staphylococcus aureus . The wound measured 7 cm in length, 5 cm in width, and 1.5 cm in depth, having purulent white edges and exudates exceeding the size of the wound. The systemic antibiotic use was opposing to improve the patient's clinical condition due to underlying nephrotoxicity that may have deteriorated renal failure and resistance of the infecting pathogen. The halogenated taurine (Tau) derivatives N-chlorotaurine (NCT) and N-bromotaurine (NBrT) with potent anti-inflammatory and antimicrobial efficacy were alternatively employed as combination topical treatment to provide a therapeutic solution. Each agent was applied separately with an interval of 5 minutes as a 1% spray in aqueous solution every 30 minutes during the day for 3 days. This treatment was very well tolerated and led to rapid disappearance of the purulent exudate, rapid epithelialization, and complete healing. To avoid relapse, the application was continued 4 times daily for a further 4 days. No complications occurred in the course of treatment. This case report confirms the therapeutic efficacy of NCT in chronic purulent wounds. NBrT is well tolerated, too, and can be used in combination with NCT in emergency clinical settings. Its potential as a single agent should be investigated in further studies. Advancement of wound closure by these agents proved to be life-saving for this patient. Further molecular research is needed to identify mechanisms that promote wound healing.